Urogenic reactive arthritis: current aspects of diagnosis and treatment - T V Asner; Alexey Nikolayevich Kalyagin (Современная ревматология)
The paper gives an update on urogenic reactive arthritis, which will be useful for practitioners during their work with patients with articular pathology.